[A3X][Ga3PS8] (A = K, Rb; X = Cl, Br): promising IR non-linear optical materials exhibiting concurrently strong second-harmonic generation and high laser induced damage thresholds. Issue 9 (28th June 2016) - Liu, Bin-Wen; Zeng, Hui-Yi; Jiang, Xiao-Ming; Wang, Guan-E; Li, Shu-Fang; Xu, Li; Guo, Guo-Cong
Abstract : We have developed a new series of salt-inclusion chalcogenides, which are promising IR-NLO materials exhibiting large second-harmonic generation and high laser-induced damage thresholds. Abstract : Mid-far infrared (IR) non-linear optical (NLO) materials are of great importance in military and civil fields. However, commercial IR-NLO crystals (such as AgGaS2, AgGaSe2 and ZnGeP2 ) do not currently satisfy the requirements of large second-harmonic generation (SHG) and high laser induced damage thresholds (LIDTs), which seriously limits their practical applications. Herein, we have developed a new series of salt-inclusion chalcogenides, [A3 X][Ga3 PS8 ] (A = K, Rb; X = Cl, Br), which are constructed from alternate stacking of adamantane-like [Ga3 PS10 ] 6− cluster layers and cationic [A3 X] 2+ salt layers. Importantly, they display both large SHG responses of several-fold and high LIDTs for dozens of times that of commercial AgGaS2, which exhibit the highest LIDTs among the reported IR-NLO materials with a larger SHG conversion efficiency than that of AgGaS2 . These properties together with wide transparent region, type I phase-matching features and congruent-melting behaviors indicate they are promising IR-NLO materials.